2020
DOI: 10.1177/0162643420947826
|View full text |Cite
|
Sign up to set email alerts
|

Using Assistive Technology to Support Science Instruction in the Inclusive Elementary Classroom

Abstract: In 2004, the Individuals with Disabilities Education Act outlined specific considerations for students with individual education programs in relation to their needs and application of assistive technology (AT) devices and services used to access school curriculum. Teachers will interact with a variety of assistive technologies during their career and must have an understanding of how their individual students are accessing lessons and school-based activities. This practitioner article presents a vignette about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Lastly, the special education teachers recommended providing basic computer literacy skills to students with disabilities prior to attempting to integrate technology into their education. This suggestion notably aligns to the conclusion of a research study conducted by Taylor et al (2020).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Lastly, the special education teachers recommended providing basic computer literacy skills to students with disabilities prior to attempting to integrate technology into their education. This suggestion notably aligns to the conclusion of a research study conducted by Taylor et al (2020).…”
Section: Discussionsupporting
confidence: 89%
“…The preservice teachers did not have the opportunity to interact with the students prior to the implementation, therefore the students might have been more comfortable if they had worked with their usual class teachers. Although the literature (e.g., Atanga et al, 2020;Kutlu et al, 2018;Taylor et al, 2020;Thomas et al, 2019) has stressed teachers' lack of technology knowledge and the implementation of such technologies in the special education context as being sources of the challenges observed, the current study found that students' lack of technological knowledge and skills were also reported by the special education teachers who observed the implementations. This finding supports the study of Taylor et al (2020) who noted that successful instruction using technologies could only be achieved if both the teachers and their students have sufficient prior knowledge of relevant technology use.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Assistive technology in the inclusive classroom significantly impacts performance and attitude in teaching mathematics (Wairimu, Chomba, and Awori, 2018). The use of technology to support students suffering from autism increases their engagement and motivation in science education, especially in Biology (Taylor, Lohmann, and Kappel, 2022).…”
Section: Impact Of Using Technology For Assisting Students With Speci...mentioning
confidence: 99%
“…AT tools may be low-tech, mid-tech, or high-tech and IEP teams should select the device/service that is most appropriate for the specific student (Dell et al, 2017). Assistive technologies should be meaningfully and intentionally incorporated into daily classroom instruction in both the general education and special education classrooms (Taylor et al, 2020). In addition, many students will need to use these same AT tools to participate in activities in the home and community, demonstrating the need for schools to collaborate with families to support student AT use outside the classroom setting.…”
Section: Research-article2021mentioning
confidence: 99%